Analytical Dashboard Information System Audit Using COBIT 5 Framework to Support PT Vinix Seven Aurum's Decisions - Chamila Meyra Aziza; Nina Sulistiyowati; Apriade Voutama (Universitas Mohammad Husni Thamrin, 2026)
The development of information technology encourages organizations to utilize information systems to support data management and decision-making processes. One form of information technology utilization is the use of analytical dashboard applications that can present information visually and in an integrated manner, enabling management to monitor organizational performance and conditions more effectively. However, the use of information systems needs to be evaluated periodically to ensure that the system is managed effectively, efficiently, and in accordance with good information technology governance principles. This study aims to conduct an information system audit of the analytical dashboard application at PT Vinix Seven Aurum using the COBIT 5 framework with a focus on the Deliver, Service and Support (DSS) domain, particularly DSS01, DSS02, and DSS03. The research method used is a quantitative descriptive method with data collection techniques including observation, interviews, and questionnaire distribution to parties involved in information system management. Data analysis was carried out using the COBIT 5 Process Capability Model to determine the capability level of the existing information technology processes. The results show that the management of information systems in the DSS domain has been running fairly well; however, there are still several gaps between the current conditions and the expected capability level. Therefore, improvements are needed in several aspects of system management. The results of this study are expected to provide recommendations for organizations to improve the effectiveness of information technology governance so that the analytical dashboard system can support decision-making processes more optimally.